2014
DOI: 10.3389/fnmol.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Systemic gene delivery to the central nervous system using Adeno-associated virus

Abstract: Adeno-associated virus (AAV)-mediated gene delivery has emerged as an effective and safe tool for both preclinical and clinical studies of neurological disorders. The recent discovery that several serotypes are able to cross the blood–brain barrier when administered systemically has been a real breakthrough in the field of neurodegenerative diseases. Widespread transgene expression after systemic injection could spark interest as a therapeutic approach. Such strategy will avoid invasive brain surgery and allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 81 publications
0
44
1
1
Order By: Relevance
“…In such cases, where neurological tissue, or expansive, difficult to reach tissue must be studied or treated, a dual vector AAV system may be unnecessarily cumbersome to administer in a broad range of experimental and clinical settings as opposed to a single vector virus. 32 In such cases, the development of single vector variants of activators serves well in terms of utility for future applications. As such, while this manuscript was under preparation, a similar work was published demonstrating feasibility of delivering a Cas9 activator in a singular AAV vector.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, where neurological tissue, or expansive, difficult to reach tissue must be studied or treated, a dual vector AAV system may be unnecessarily cumbersome to administer in a broad range of experimental and clinical settings as opposed to a single vector virus. 32 In such cases, the development of single vector variants of activators serves well in terms of utility for future applications. As such, while this manuscript was under preparation, a similar work was published demonstrating feasibility of delivering a Cas9 activator in a singular AAV vector.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain conditions, it may also be possible to obtain therapeutic effects through noninvasive intravenous delivery of stem cells [149,214] , thus suggesting that systemic delivery may be a feasible option at least with particular stem cell types and in situations where the integrity of the blood brain barrier is compromised. Furthermore, several AAV serotypes can cross the BBB and provide transgene expression during systemic delivery (reviewed in [215] ). Intravenous delivery of gene therapy vectors and stem cells thus avoids invasive brain surgery and might be particularly promising for CNS diseases involving multiple brain regions affected by the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A major focus of recent gene therapy research has been in developing brain-tropic AAV vectors and understanding the mechanisms of their passage across the BBB. [143] AAV9 vectors are well tolerated IV viral vectors that can cross the endothelial cells of the BBB [144,145] via active-transport, while not compromising barrier integrity [146] and have promising results in clinical trials for their safety and their efficiency to transduce target cells, for example, in spinal muscular atrophy therapy [147][148][149], spinal muscle atrophy [150], and mucopolysaccharidosis IIIB (Sanfilippo syndrome) [151,152]. Zhang and coworkers showed that another four serotypes of recombinant AVV can also overcome the BBB: rAAVrh.10, rAAVrh.39, rAAVrh.43, and rAAV7 [153].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%